Museum of Contemporary Art Tokyo : Selected works from Museum of Contemporary Art Tokyo 1995. - Hashimoto, Keiko; Hayashi, Yoko; Hirano, Chieko; Kato, Hiroko; Kumagai, Isako; Minami, Yusuke; Miyashita, Kikuro; Mori, Chika; Noguchi, Reiichi; Oga, Yosuke; Otoba, Satoshi; Saito, Yasuyoshi; et al. (Tokyo : Museum of Contemporary Art, 1995)
AI-O ; Arakawa, Shusaku ; Aso, Saburo ; Boltanski, Christian ; Borofsky, Jonathan ; Caro, Anthony ; Christo ; Cragg, Tony (Anthony) ; Dine, Jim ; Ei-Kyu ; Endo Toshikatsu ; Enokura, Koji ; Fischl, Eric ; Riverhead (New York) ; Fontana, Lucio ; Funakoshi, Katsura ; Hagiwara, Hideo ; Hamada, Chimei ; Hamaguchi, Yozo ; Hikosaka, Naoyoshi ; Hiramatsu, Reiji ; Hockney, David ; Hori, Kosai ; Horiuchi, Masakazu ; Ikeda, Masuo ; Imaï, Toshimitsu ; Inoue, Bukichi ; Isobe, Yukihisa ; Ito, Kosho ; Iwahashi, Eien ; Judd, Donald ; Kawamata, Tadashi ; Kawara, On ; Kelly, Ellsworth ; Kiefer, Anselm ; Kikuhata, Mokuma ; Kim, Tschang-Yeal ; Klein, Yves ; Kojima, Nobuaki ; Komai, Tetsuro ; Koons, Jeff ; Koshimizu, Susumu ; Kudo, Tetsumi ; Kusama Yayoi ; Kuwayama, Tadaaki ; Lee, U-Fan ; Lichtenstein, Roy ; Long, Richard ; Louis, Morris ; Mangold, Robert ; Marden, Brice ; Martin, Agnes ; Matsumoto, Yoko ; Mori, Yoshio ; Morimura, Yasumasa ; Motonaga, Sadamasa ; Murai, Masanari ; Muraoka Saburo ; Murray, Elizabeth ; Nakabayashi, Tadayoshi ; Nakamura, Hiroshi ; Nakamura, Teii ; Nakanishi, Natsuyuki ; Nambata, Tatsuoki ; Noda, Tetsuya ; Noland, Kenneth ; Ogura, Yuki ; Ono, Hidetaka ; Onosato, Toshinobu ; Paik, Nam June ; Park, Seo-Bo ; Rauschenberg, Robert ; Richter, Gerhard ; Rothko, Mark ; Saito, Yoshishige ; Schnabel, Julian ; Shigi, Go ; Shimomura, Ryonosuke ; Shinohara, Ushio ; Shiraga, Kazuo ; Smithson, Robert ; Stella, Frank ; Suga, Kishio ; Sugai, Kumi ; Sultan, Donald ; Tabuchi, Yasukazu ; Tada, Minami ; Takamatsu, Jiro ; Takayama, Tatsuo ; Tanaka, Atsuko ; Tatehata, Kakuzo ; Tatsuno, Toeko ; Tomio, Miki ; Toya, Shigeo ; Tsuruoka, Masao ; Ueda, Kaoru ; Wakabayashi, Isamu ; Warhol, Andy ; Wesselmann, Tom ; Yamada, Masaaki ; Yamaguchi, Katsuhiro ; Yamaguchi, Takeo ; etc.
biog. per kunstenaar
Engels & Japans
boek